Presentations, Complications, and Challenges Encountered During Management of Type 1 Diabetes in Egyptian Children During COVID-19 Pandemic: A Single-Center Experience - Abdou, Marise; Hassan, Mona M.; Hassanein, Samah A.; Elsebaie, Eman H.; Shamma, Radwa A. (Frontiers in Endocrinology, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic has been associated with significant challenges pertaining to the management of children and adolescents with type 1 diabetes (T1D). Issues such as fear of infection and lockdown measures have resulted in delayed and more severe clinical presentations of this disease. Objectives This study aimed at reporting the frequency and severity of diabetic ketoacidosis (DKA) and the rate of DKA complications in children with diabetes who presented to the emergency unit during COVID-19 pandemic. Furthermore, the purpose of this study was to compare the data collected from the first and second COVID-19 waves with that of the pre-COVID-19 period and describe the challenges encountered during disease management. Methods This cross-sectional study included all children and adolescents with T1D who presented to the emergency department at Abo El Rish Children’s Hospital, Cairo University, during the first and second COVID-19 waves. It also included data collected from the pre-COVID-19 period. Demographic and clinical data, investigations, and management details were collected from the patients’ medical records. Results Three hundred twenty-four Egyptian children and adolescents diagnosed with T1D were recruited. One hundred forty patients (43.2%) presented with severe DKA, and approximately 66% were newly diagnosed with T1D. The participants presented with manifestations suggestive of COVID-19, such as fever (29.5%), respiratory manifestations (7.2%), and gastrointestinal symptoms (14.7%). Thirty-seven patients were tested for severe acute respiratory syndrome coronavirus 2 infection using nasopharyngeal swabs, and four patients tested positive. Around 18% of patients developed hypokalemia during disease management. A comparison between these data and the data from previous years revealed that there was a significant increase in the number of newly diagnosed cases with more severe DKA at presentation and a higher frequency of development of hypokalemia during both COVID-19 waves. Conclusion An increase in the frequency of newly diagnosed cases was identified during the first and the second COVID-19 waves compared with the pre-COVID-19 period. The patients presented with more severe DKA, probably due to a more delayed presentation. The frequency of hypokalemia development was also significantly higher, and the severity of DKA was associated with a longer ICU admission. Further studies are required to establish a definitive link between the COVID-19 pandemic and the severity of presentation.